FORMS AND FUNCTIONS OF PRONOMINALS IN MIDDLE YALI - YUSUF W. SAWAKI (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2007)
Abstract This paper aims at describing pronominal forms in Middle Yali, a Papuan language of Trans-New Guinea phylum. The language has two kinds of pronominals, i.e. independent pronouns and dependent counterparts. The language applies a set of 6 independent pronouns, which identify first, second and third person, with singular/plural number. The more interesting kind is the dependent pronouns, which may be considered as one of salient features of Middle Yali grammar. On various verb types, they attach to mark agent/subject and patient/object; while, on nouns, dependent pronouns function to mark possessive markers. It is also true for adjectives and postpositions where dependent pronouns mark prefixed-person markers. Keywords: pronominals, independent pronouns, dependent pronouns.